A High Dielectric N‐Type Small Molecular Acceptor Containing Oligoethyleneglycol Side‐Chains for Organic Solar Cells2. Issue 3 (11th January 2018) - Jang, Bomee; Lee, Changyeon; Lee, Young Woong; Kim, Donguk; Uddin, Mohammad Afsar; Kim, Felix Sunjoo; Kim, Bumjoon J.; Woo, Han Young
Abstract : We report a new small molecular acceptor, ITIC‐OEG, which is based on indacenodithieno[3, 2‐ b ]thiophene and 1, 1‐(dicyanomethylene)‐3‐ indanone including oligoethyleneglycol (OEG) side‐chains. ITIC‐OEG was found to have higher dielectric constant ( ε r =5.6) than that of a reference molecule of ITIC with normal alkyl substituents ( ε r =3.9). The dielectric constant of medium influences significantly the exciton binding energy and the resulting charge separation and recombination. The optical, electrochemical and morphological properties of ITIC‐OEG and its photovoltaic characteristics were investigated by blending with a semi‐crystalline donor polymer, PPDT2FBT, with comparison to those of ITIC. ITIC‐OEG shows more red‐shifted absorption and stronger crystalline packing than ITIC. However, the lower photovoltaic performance (with 1.58% power conversion efficiency, PCE) was measured for PPDT2FBT:ITIC‐OEG, compared to PPDT2FBT:ITIC (5.52% PCE). The incompatibility between PPDT2FBT and ITIC‐OEG (due to high hydrophilic nature of OEG chains) resulted in poor intermixing with large domain separation over 300 nm, showing inefficient charge separation and significant charge recombination. Therefore, to investigate the effect of dielectric constant of the materials on the charge separation and recombination, the blend morphology of the PPDT2FBT:ITIC‐OEG should be optimized first by improving their miscibility and phase separation. Abstract : A new nonfullerene acceptor, ITIC‐OEG was synthesized by replacing the normal alkyl substituents with OEG side‐chains and the dielectric constant was greatly enhanced. The incompatibility between PPDT2FBT and ITIC‐OEG (due to high hydrophilic nature of OEG chains) resulted in poor blend morphology, showing inefficient charge separation and significant charge recombination with small J SC and PCE.